Development of Sn-Cu filled activated carbon composite solder via powder metallurgy technique - Sayyidah Amnah Musa (School of Materials Engineering, 2016)
In this research, Sn-0.7Cu solder will be added with AC particles and fabricated via powder metallurgy techniques which comprise of mixing, compacting and sintering process. The synthesis of lead-free composite solder was prepared via optimization of process parameter for powder metallurgy technique (Phase 1). In the mixing process, the mixing speed will be constant at 200 rpm but the mixing time was varied from 1 to 5 hours. The compaction loads parameter were 217, 260, 303, 347 and 390 MPa, meanwhile the optimization of sintering time is 107, 116, 124, 132 and 141 s. According to the preeminent parameter acquired from the optimization process, the selected parameter for mixing, compacting and sintering was 1 h, 390 MPa and 180 p0sC. Following the optimization from the Phase 1, the samples were then prepared for the characterization testing but with different percentages composition of AC particles addition into solder matrix (Phase 2). The percentages of AC particles added into Sn-0.7Cu composite solder were approximately about 0, 0.05, 0.10, 0.15 and 0.20 wt. %. The investigation involved for the Phase 2 was including with the bulk composite solder and composite solder joint. The bulk Sn-0.7Cu-AC composite solders was carried out with the melting temperature, phase analysis, resistivity and hardness test. The composite solder was then reflowed to make a joint and the composite solder joint have investigated for the wettability, shear strength and microstructural analysis.